2017
DOI: 10.1093/cid/cix986
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Antibiotic Use Among Adults With Uncomplicated Community-Acquired Pneumonia Requiring Hospitalization in the United States

Abstract: In this nationwide sample of patients hospitalized for CAP, median total LOT was just under 10 days, with more than 70% of patients having likely excessive treatment duration. Better adherence to recommended CAP therapy duration by improving prescribing at hospital discharge may be an important target for antibiotic stewardship programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 20 publications
2
44
3
2
Order By: Relevance
“…Our data are consistent with those of Scarpato et al, 15 who noted a similar fluoroquinolone prescribing rate of 23.5% when evaluating discharge prescriptions from the Hospital of the University of Pennsylvania. Our fluoroquinolone prescribing rate was lower than the 40% rate described by Yogo et al 8 for discharge prescriptions filled within 7 days posthospitalization, lower than the 47%-49% rate of outpatient prescribing noted in a study of community acquired pneumonia by Yi et al, 24 and lower than the 30.5% rate cited by Vaughn et al 25 from patients diagnosed with urinary tract infection or community-acquired pneumonia in 48 hospitals in the Michigan Hospital Medicine Safety Consortium. 1,8,24,25 The inpatient stewardship programs at all 3 study hospitals were actively engaged in initiatives to decrease inpatient fluoroquinolone prescribing due to resistance of common pathogens to these agents and the increased risk Clostridioides difficile infections.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Our data are consistent with those of Scarpato et al, 15 who noted a similar fluoroquinolone prescribing rate of 23.5% when evaluating discharge prescriptions from the Hospital of the University of Pennsylvania. Our fluoroquinolone prescribing rate was lower than the 40% rate described by Yogo et al 8 for discharge prescriptions filled within 7 days posthospitalization, lower than the 47%-49% rate of outpatient prescribing noted in a study of community acquired pneumonia by Yi et al, 24 and lower than the 30.5% rate cited by Vaughn et al 25 from patients diagnosed with urinary tract infection or community-acquired pneumonia in 48 hospitals in the Michigan Hospital Medicine Safety Consortium. 1,8,24,25 The inpatient stewardship programs at all 3 study hospitals were actively engaged in initiatives to decrease inpatient fluoroquinolone prescribing due to resistance of common pathogens to these agents and the increased risk Clostridioides difficile infections.…”
Section: Discussioncontrasting
confidence: 68%
“…Our fluoroquinolone prescribing rate was lower than the 40% rate described by Yogo et al 8 for discharge prescriptions filled within 7 days posthospitalization, lower than the 47%-49% rate of outpatient prescribing noted in a study of community acquired pneumonia by Yi et al, 24 and lower than the 30.5% rate cited by Vaughn et al 25 from patients diagnosed with urinary tract infection or community-acquired pneumonia in 48 hospitals in the Michigan Hospital Medicine Safety Consortium. 1,8,24,25 The inpatient stewardship programs at all 3 study hospitals were actively engaged in initiatives to decrease inpatient fluoroquinolone prescribing due to resistance of common pathogens to these agents and the increased risk Clostridioides difficile infections. 26,27 Based on this growing body of literature incorporating postdischarge antibiotics, ASPs should focus on discharge processes as a key area to promote avoidance of fluoroquinolones and shorter, syndrome-based durations.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…However, despite current evidence avoiding unnecessarily prolonged treatments remains an arduous task, likely due to a false sense of security provided by longer-term treatments [21]. In fact, a retrospective study carried out in the United States in patients admitted for CAP, observed that the average duration of antibiotic treatment exceeded the recommended time by 74 and 71% for patients aged 18-64 years and ≥ 65 years, respectively [22]. A remarkable strength of this study is that it is based on a clinical trial with a unique design where the doctor him or herself decided on the type of antibiotic and in which similar cure rates were obtained for both groups.…”
Section: Discussionmentioning
confidence: 99%
“…In einer vorläufigen Analyse einer multizentrischen Studie zu Qualitätsindikatoren im Bereich Antibiotikaverordnung in deutschen Krankenhäusern (eigene, unveröffentlichte Daten) wurde im Bereich ambulant erworbener Pneumonien beispielsweise eine erstaunlich lange Behandlungsdauer beobachtet (verglichen mit der Leitlinienempfehlung von 5-7 Tagen). Eine ebenfalls lange mittlere Behandlungsdauer von > 8 Tagen bei stationären Patienten mit ambulant erworbener Pneumonie wurde auch in anderen Studien ermittelt [8]. Häufig zu lange Behandlungen findet man auch bei der perioperativen Prophylaxe, wenn sie postoperativ weitergegeben wird oder gar inadäquat über > 24 Stunden hinaus verlängert wird [9,10].…”
Section: Optimierungsbereicheunclassified